THE EFFECT OF DISCRIMINATION ON BLACK PEOPLE IN RALPH ELLISON’S INVISIBLE MAN - Paskahlinno Zalvatore Hendrik; Ceisy N Wuntu; Sanerita T Olii (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study has the purpose to finding out the effects of discrimination on black people as reflected in the novel Invisible Man by Ralph Ellison.This study is categorized as qualitative research because the data are in the form of words, statements and quotation from some sources. In analyzing this novel the writer used expressive approach which is only focused on the expression, overflow, utterance of feelings of the writer's itself on Invisible Man novel especially the discrimination experienced by main character Ralph Ellison which has to do with teaching moral lessons to society.The result to be drawn from a study of the Invisible Man is that the narrator only understands he was seeking his identity in the incorrect spot after a sequence of discrimination events. Invisible Man was searching for a definition in the eyes of others especially in whites views, and he continued attempting to find himself by adopting other people's paths. As a result, no matter what he accomplished, he has always been invisible about himself and everyone. The reader can capture the mental and physical suffering by the narrator experiences as a result of this struggle as the author uses clear adjectives. In the context of this adjective it can convince the reader that this passage is about the narrator going crazy. He experiences big reactions to small details like ringing noises and itchy skin.